Truncating Variant in Myof Gene Is Associated With Limb-Girdle Type Muscular Dystrophy and Cardiomyopathy - Kiselev, Artem; Vaz, Raquel; Knyazeva, Anastasia; Sergushichev, Alexey; Dmitrieva, Renata; Khudiakov, Aleksandr; Jorholt, John; Smolina, Natalia; Sukhareva, Ksenia; Fomicheva, Yulia; Mikhaylov, Evgeny; Mitrofanova, Lubov; et al. (Frontiers in Genetics, 2019)
Even though genetic studies of individuals with neuromuscular diseases have uncovered the molecular background of many cardiac disorders such as cardiomyopathies and inherited arrhythmic syndromes, the genetic cause of a proportion of cardiomyopathies associated with neuromuscular phenotype still remains unknown. Here, we present a clinical case with a combination of cardiomyopathy and limb-girdle type muscular dystrophy where whole exome sequencing identified myoferlin (MYOF) – a member of the Ferlin protein family and close homolog of DYSF - as the most likely candidate gene. The disease-causative role of the identified variant c.[2576delG; 2575GC], p.G859fs is supported by functional studies in vitro using primary patient’s skeletal muscle mesenchymal progenitor cells, including both RNA sequencing and morphological studies, as well as recapitulating of muscle phenotype in vivo in zebrafish experiments. We provide the first evidence supporting a role of MYOF in human muscle disease.